The Impact of Inflation on Long-Term Housing Loans - Ingo E. Tschach (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2000)
The extension of long-term loans, e.g. to finance housing, is adversely affected by inflation. For one thing, the higher nominal interest rates charged by the banks in response to inflation mean that borrowers have to make (nominally) higher interest payments, which unnecessarily reduces their borrowing capacity. For another, long-term loans with variable interest rates increase the probability that borrowers will become unable to meet their payment obligations. The present paper examines these two assertions in detail. At the same time, it presents a concept for substantially reducing the weaknesses of conventional lending methodologies. We start by investigating the consequences of a stable inflation rate on the borrowing capacity of credit clients, then go on to analyze the impact of fluctuating inflation rates on the risk of default.
urn:nbn:de:hebis:30-18498
Keywords: 330